New fluorescent bile acids: Synthesis, chemical characterization, and disastereoselective uptake by Caco-2 cells of 3-deoxy 3-NBD-amino deoxycholic and ursodeoxycholic acid - LONG, AIDEEN; GILMER, JOHN; EHRHARDT, CARSTEN; WANG, JUN; SALOMON, JOHANNA JESSICA; MAJER, FERENC; KEAVENY, RAYMOND; SHARMA, RUCHIKA (My University, 2012)
Deoxycholic acid (DCA), a secondary bile acid (BA), and ursodeoxycholic acid (UDCA), a tertiary BA, cause opposing effects in vivo and in cell suspensions. Fluorescent analogues of DCA and UDCA could help investigate important questions about their cellular interactions and distribution. We have prepared a set of isomeric 3?- and 3?-amino analogues of UDCA and DCA and derivatised these with the discrete fluorophore, 4-nitrobenzo-2-oxa-1,3-diazol (NBD), forming the corresponding four fluorescent adducts. These absorb in the range 465?470 nm and fluoresce at approx. 535 nm. In order to determine the ability of the new fluorescent bile acids to mimic the parents, their uptake was studied using monolayers of Caco-2 cells, which are known to express multiple proteins of the organic anion-transporting peptide (OATP) subfamily of transporters. Cellular uptake was monitored over time at 4?C and 37?C to distinguish between passive and active transport. All four BA analogues were taken up but in a strikingly stereo- and structure-specific manner, suggesting highly discriminatory interactions with transporter protein(s). The ?-analogues of DCA and to a lesser extent UDCA were actively transported, whereas the ?-analogues were not. The active transport process was saturable, with Michaelis-Menten constants for 3?-NBD DCA (5) being Km = 42.27?12.98 ?M and Vmax = 2.8?0.4 nmol/(mg protein?min) and for 3?-NBD UDCA (3) Km = 28.20?7.45 ?M and Vmax = 1.8?0.2 nmol/(mg protein?min). These fluorescent bile acids are promising agents for investigating questions of bile acid biology and for detection of bile acids and related organic anion transport processes.
PUBLISHED
Keywords: Biochemistry; Deoxycholic acid (DCA)